Perspektif Teologis tentang Sihir dalam Kisah Nabi Musa: Studi Tafsir Anwār Al-Tanzīl Wa Asrār Al-Ta’wīl Karya Al-Baidawi - Chafidul Mubaroq; Eka Prasetiawati; Wahyudi Wahyudi (Medan Resource Center, 2026)
This study examines the concept of magic in the story of Prophet Musa as interpreted by Al-Baidawi in Anwār al-Tanzīl wa Asrār al-Ta’wīl, focusing on Surah Ṭāhā verses 65–70. Although the theme of magic has been widely discussed in Islamic scholarship, limited attention has been given to Al-Baidawi’s exegetical perspective, particularly regarding the distinction between magic and miracles in the Qur’anic narrative. This study therefore seeks to contribute to the existing literature by providing a focused analysis of Al-Baidawi’s interpretation of the confrontation between Prophet Musa and Pharaoh’s magicians. The research employs a qualitative library-based approach using descriptive-analytical methods and thematic content analysis. Data were collected from Al-Baidawi’s tafsir as the primary source and supported by relevant classical and contemporary references. The analysis involved identifying key interpretive themes, examining textual explanations, and evaluating theological arguments related to magic and miracles. The findings show that Al-Baidawi understands magic as a form of sensory deception that manipulates human perception without changing objective reality, whereas miracles are genuine manifestations of divine power bestowed upon prophets. He also regards magic as a serious religious transgression because of its association with shirk and deviation from divine guidance. Furthermore, the study highlights the psychological dimension of magical illusion reflected in Musa’s response during the encounter. These findings enrich the understanding of classical Qur’anic exegesis and offer a contextual framework for discussing perceptions of supernatural phenomena within Islamic thought.